1995
DOI: 10.1111/j.1365-3083.1995.tb03654.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Post Transplant Blood Lymphocyte Phenotype Subsets as a Marker of Rejection in Renal Allograft Recipients

Abstract: The postoperative alterations of absolute levels of lymphocyte phenotype subsets in peripheral blood were studied in recipients of living donor renal allografts and in kidney donors. The results were expressed as per cent changes of the preoperative values. The lymphocyte subsets, CD3, CD4 and CD8 cells, decreased to approximately 50% following the surgical trauma, with rapid recovery to preoperative levels within 1 week in kidney donors and in recipients without rejection episodes. In contrast, the T-cell lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Furthermore, several studies have suggested that the changes of peripheral lymphocyte subsets have previously been related to clinical events, before clinical signs of rejection, and are a predictive marker for the later occurrence of AR episode. 16,[22][23][24] Based on these studies, the onsets of increasing numbers of peripheral lymphocyte subsets may be predictive for the later occurrence of clinical AR episodes in the present study.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Furthermore, several studies have suggested that the changes of peripheral lymphocyte subsets have previously been related to clinical events, before clinical signs of rejection, and are a predictive marker for the later occurrence of AR episode. 16,[22][23][24] Based on these studies, the onsets of increasing numbers of peripheral lymphocyte subsets may be predictive for the later occurrence of clinical AR episodes in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…The changes of lymphocyte subsets have been shown to correlate with the clinical events following liver and renal transplantation 22 . An increase in CD3 and CD4 T cell counts was documented in acute cellular rejection, but the change of the B lymphocyte (CD19) population after transplantation is controversial 23,24 . Furthermore, the CD4+ CD28+ T cell is a mediator for the costimulatory signal on T cells 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, polyphenols seem to have significant potential in organ or tissue allotransplantation. Wramner et al (19) demonstrated that the lymphocyte subsets CD4ϩ and CD8ϩ cells decreased to approximately 50% after surgical trauma, with rapid recovery to preoperative levels within 1 week in recipients without rejection episodes; in contrast, the T-cell levels in recipients with rejection episodes remained low after 1 week. Davenport et al (20) demonstrated that there is a significant decrease in the CD4: CD8 ratio of T-cell subsets in peripheral blood from days 2 and 3 to day 7 after transplantation in recipients with rejection episodes.…”
Section: Discussionmentioning
confidence: 94%
“…ATG has proven to be an effective immunosuppressive drug in both experimental [15] and in clinical studies [11]. Although the mode of action of ATG-induced transplantation tolerance is not fully known, it is a fact that ATG treatment causes killing or depletion of T cells of various specificities [14,37,38]. In several reports, an active suppressor-cell mechanism has been suggested [16,17].…”
Section: Discussionmentioning
confidence: 99%